2017
DOI: 10.9744/dimensi.44.2.143-148
|View full text |Cite
|
Sign up to set email alerts
|

Glass and Perforated Metal Double Skin Façade Performance in Hot Humid Climate

Abstract: The construction of a sustainable building in Indonesia has increased in recent years. Middle-to high-rise buildings are encouraged to enhance its performance to reduce energy demands. With maximum temperature 34°C, most of the buildings in Indonesia utilize mechanical air conditioning to achieve indoor thermal comfort. In this research, the performance of campus building with Double Skin Façade (DSF) in Indonesia would be quantitatively assessed and simulated by utilizing Autodesk Revit and Green Building Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the study developed by [47], this indicator helped to choose the energy-saving strategies because thermal comfort was evaluated, and it was noticed that one strategy, which recorded a great energy performance, negatively impacted thermal comfort during the summer season. N. Ardiani et al [74] showed that achieving low energy demand and ideal thermal comfort may require several different energy-saving techniques; for this reason, a thorough investigation is necessary.…”
Section: Performance Metricsmentioning
confidence: 99%
“…In the study developed by [47], this indicator helped to choose the energy-saving strategies because thermal comfort was evaluated, and it was noticed that one strategy, which recorded a great energy performance, negatively impacted thermal comfort during the summer season. N. Ardiani et al [74] showed that achieving low energy demand and ideal thermal comfort may require several different energy-saving techniques; for this reason, a thorough investigation is necessary.…”
Section: Performance Metricsmentioning
confidence: 99%